2023
DOI: 10.9734/ijpss/2023/v35i22752
|View full text |Cite
|
Sign up to set email alerts
|

Biological Management of Lentil (Lens culinaris Medik) Fusarium wilt by Using the Potential Pseudomonas Isolates

Abstract: Lentil (Lens culinaris Medik) is also known as "massoor". A member of the Leguminaceae family is known for their high protein and nutrient content. Wilt incited by Fusarium oxysporum f.sp. lentis can result in significant yield losses upto 50% for lentil farmers. Chemical management through fungicides reduces crop losses significantly but has some environmental drawbacks and conflicts on the human health instead other methods of control such as the use of plant growth-promoting rhizobacteria (PGPR) as a bio-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…reported that Pseudomonas aeruginosa OG101 inhibited F. oxysporum mycelial growth by 24.4%. Similarly,Chaurasiya et al (2023) reported that Pseudomonas sp. PGP 18 isolate inhibited the F. oxysporium that causes lentil wilt disease by 67.41%.…”
mentioning
confidence: 93%
“…reported that Pseudomonas aeruginosa OG101 inhibited F. oxysporum mycelial growth by 24.4%. Similarly,Chaurasiya et al (2023) reported that Pseudomonas sp. PGP 18 isolate inhibited the F. oxysporium that causes lentil wilt disease by 67.41%.…”
mentioning
confidence: 93%